CHARACTERISTICS OF VISUAL LITERACY-BASED BIOLOGY LEARNING MODULE VALIDITY ON PHOTOSYNTHESIS LEARNING MATERIALS - Diini Fitrahtun Nida; Muhyiatul Fadilah; Ardi Ardi; Suci Fajrina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
Visual literacy is the skill to interpret and give meaning to information in the form of images or visuals. Visual literacy is included in the list of 21st-century skills. The observation results indicate that most of the students have not mastered visual literacy well. One of the efforts that can be made to improve visual literacy is the provision of appropriate and right teaching materials. The research is an R&D (Research and Development) using a 4-D model, which is modified to 3-D (define, design, develop). The instruments used were content analysis sheets and validation questionnaires. The results of the research imply that there are three characteristics of the validity of the developed module. First, visual literacy produces students’ critical thinking and communication skills by building their own meaning or conclusions regarding the given image object. Second, visual literacy produces students' creative thinking by recreating it in the form of images or other visual objects from the provided visual information. Third, visual literacy produces students' critical thinking skills by connecting visual objects or images that are distributed to them. The module is considered to be very valid (feasible) to use with a percentage of 94.23%.